Classification of children with learning problems and the establishment of special classes in Delaware from the 1930s to the mid-1940s. - Yoshii, Ryo (Paedagogica Historica, 2019)
This study focuses on J. E. Wallace Wallin, who recognised the rights of children with disabilities to receive an education, and who tackled the scientific classification of children and the provision of special classes in the state of Delaware from the 1930s to the middle of the 1940s. This study intends to clarify how Wallin recognised and classified children who exhibited learning problems, and how he provided an educational environment for them. Wallin advocated the democratic philosophy of providing differentiated education based on the individual differences among children. He classified children with learning problems as "mentally deficient", "backward", and "special subject-matter disabilities". He also recommended special educational treatment in not only special classes but also regular classes. He insisted that regular class teachers and special class teachers share the responsibility of educating children with disabilities. However, in addition to tailoring education based on the diversity exhibited by children with learning problems, it is essential to tailor it for disabled children in public school special classes established in their communities. In terms of both human and material resources, it was difficult to address learning problems suitably in regular classes while improving the quality and quantity of education in special classes.